FRI0569-HPR The Effectiveness of Education and Aerobic Exercise in Higher Functioning Patients with Fibromyalgia: an Evaluation of A New Service. (10th June 2014) - Cullinane, C.; McVeigh, J.G.; Sheehy, C.; Irundaj, B.
Abstract : Background: Fibromyalgia syndrome (FMS) is characterised by chronic widespread pain, fatigue and reduced physical function. Exercise has positive effects on physical function, fatigue and well-being in FMS 1 . However, patients find it difficult to engage in exercise and often have low self-efficacy for exercise. Objectives: The aim of this study was to evaluate a new early access service consisting of a 6-week education and aerobic exercise intervention in patients with FMS, who were classified as "high functioning". Methods: Participants (n=32) were referred from WRH rheumatology department and attended a 6-week exercise and education intervention delivered by physiotherapist and occupational therapist. Participants completed the Fibromyalgia Impact Questionnaire (FIQ), Hospital Anxiety and Depression Score (HAD) Six-Minute-Walk Test (6MWT) and Exercise Self-Efficacy Scale (ESES). Follow up was carried out post and 3 months post programme. Results: Participants who completed the intervention had a significant improvement in mean (SD) pain from baseline 7.01 (1.8) to the end of the programme 5.6 (2.9), p=0.03. Mean (SD) 6MWT improved from 386m (96) to 416m (57) at the end of the programme (p=0.05), this was maintained at 3 month follow-up. There was no significant change in total FIQ score or the HAD scale, however, participants' exercise self-efficacy significantly improved from 58.2 (18.6) to 68 (11.6), p=0.01. Conclusions: Improvements were recorded post programme in exercise capacity, exercise self-efficacy and VAS pain. Improvement was maintained at 3 months follow up. Anticipated service developments are use of FIQ to subgroup 2, longer term follow up, vocational rehabilitation and pedometer use to evaluate exercise adherence. 3 References: Hauser, W., Klose, P., Langhorst, J., Moradi, B., Steinbach, M., Schiltenwolf, M. & Busch, A. (2010) Efficacy of different types of aerobic exercise in fibromyalgia syndrome: a systematic review and meta-analysis of randomized controlled trials. Arthritis Research & Therapy, 12(3), R79. De Souza, (2009) Fibromyalgia Subgroups: Profiling distinct subgroups using the Fibromyalgia Impact Questionnaire. A Preliminary Study. Rheumatology Int.29:509-515 Tudor-Locke C., Craig C., Aoyagi Y., (2011). How many steps/day are enough? For older adults and special populations. A literature Review. International Journal of Behavioural Nutrition and Physical Activity 8:80 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2931